Taxonomic status of Xyrosaris melanopsamma Meyrick, 1931 (Lepidoptera: Yponomeutidae) with notes on congeneric species in East Asia - Ponomarenko, Margarita G.; Sinev, Sergey Yu. (Zootaxa, 2024)
The species Xyrosaris melanopsamma Meyrick, 1931, stat. rev. is reinstated from synonymy with X. lichneuta Meyrick, 1918 based on morphological analysis of the female genitalia. The association of conspecific males and females of X. melanopsamma is confirmed by molecular analysis using a fragment of the mtCOI gene and by studying material reared from larvae collected in the local population on Rikord Island. The genitalia of both sexes are illustrated. The recently described species X. vaginata Bae et Na, 2024 is treated as a junior subjective synonym of X. melanopsamma Meyrick, 1931. An annotated checklist of Xyrosaris spp. from East Asia is provided.